(untitled) (International Journal of Engineering and Computer Science, 2014)
The privacy-preservation in social networks is major problem in now-a-days. In distributed setting the complex data is divide between several data holders. The target is to appear at an anonymized view of the unified network without illuminating to any of the data holders information about links between nodes that are hold by other data holders. To that finish, in centralized setting two variants of an anonymization algorithm are offered which is based on sequential clustering (Sq). Proposed algorithms substantially break the SaNGreeA algorithm due to Campan and Truta which is the primary algorithm for achieving anonymity in networks by means of clustering and then secure distributed versions of algorithms. To the top of awareness, this is the earliest study of privacy preservation in distributed social networks. Finally, conclude by outlining potential research proposals in that path.